Asymmetric Dearomatization of Indoles through a Michael/Friedel–Crafts‐Type Cascade To Construct Polycyclic Spiroindolines1. Issue 13 (3rd February 2015) - Zhao, Xiaohu; Liu, Xiaohua; Mei, Hongjiang; Guo, Jing; Lin, Lili; Feng, Xiaoming
Abstract A highly efficient asymmetric dearomatization of indoles was realized through a cascade reaction between 2‐isocyanoethylindole and alkylidene malonates catalyzed by a chiral N, N′‐dioxide/MgII catalyst. Fused polycyclic indolines containing three stereocenters were afforded in good yields with excellent diastereo‐ and enantioselectivities through a Michael/Friedel–Crafts/Mannich cascade. When 2‐substituted 2‐isocyanoethylindoles were used, spiroindoline derivatives were obtained through a Michael/Friedel–Crafts reaction.